Accelerating Food Downstreaming in South Sumatra: Challenges of Cross-Sector Coordination and Local Bureaucratic Reform - Orce Kabunggul; Lukman Hakim (CV. GovPlan Indonesia, 2026)
This study aims to examine the acceleration of food downstreaming in South Sumatra, focusing on the challenges of cross-sectoral coordination and local bureaucratic reform. Despite South Sumatra’s historical position as a national food barn, the region faces structural obstacles, namely the “commodity curse” characterized by a persistent reliance on raw material exports and a significant value gap between primary agricultural sectors and the food processing industry. Utilizing a literature review and policy analysis approach, this research adopts the Collaborative Governance framework and New Institutionalism theory to dissect bureaucratic bottlenecks. Data analysis, supported by 2025 BPS and Bank Indonesia reports, reveals a profound disparity in sectoral indices, where the primary sector remains at an index of 149.63 compared to 231.73 in the food and beverage industry, accompanied by a high standard deviation of 41.59. The analysis identifies silo mentality and rigid bureaucratic structures as the primary hindrances to investment and value-added creation. The study concludes that achieving food sovereignty and economic independence requires a transformative strategy through a Task Force for downstreaming, shared Key Performance Indicators (KPI) across agencies, community-based industrial clusters, and aggressive fiscal incentives. Facilitative leadership is deemed essential to orchestrate these reforms, ensuring that South Sumatra transitions from a raw material supplier to a competitive food industrial hub, thereby maximizing economic benefits for local communities.